Improving The Service Life of Road Concrete Under The Effect of Mineral and Chemical Additives (Texas Journal of Engineering and Technology, 2026)
In the Republic of Uzbekistan, the construction of modern toll roads and highways represents a key infrastructure component that ensures the efficient functioning of transport networks globally. While asphalt and concrete materials traditionally used in road construction have proven somewhat effective, they face challenges related to long-term strength, durability, and environmental impact. This study analyzes composite materials that are fundamentally transforming road and highway construction practices and highlights their potential to overcome existing issues. It evaluates the operational efficiency of complex modified materials in road construction, emphasizing how mineral and chemical additives enhance concrete and pavement strength, resistance to deformation, cold, and aggressive environments. The findings indicate that employing these materials can extend infrastructure service life, reduce maintenance costs, and support environmental sustainability.